The takeoff in the long jump & other running jumps - Hay, J. (coachesinfo.com, 1999)
Despite its importance to success in the long jump, the takeoff has been accorded little attention by sports biomechanists. We conducted a study to determine the characteristics of an athlete's technique that determine the vertical velocity gained during the takeoff. We found that the vasti, soleus and gastrocnemius experienced a lengthening-shortening sequence of actions during the takeoff and that enhancement due to use of the stretch-shorten cycle did not make a significant contribution to the vertical velocity developed via these muscles. Standing and running vertical jumps from a two-feet takeoff were found to involve different modes of muscle action. Running long and vertical jumps and sprinting involve almost identical modes of muscle action. The results of our study of the long jump appear, therefore, to apply to running jumps in general and to sprint running.